2010
DOI: 10.1016/j.mce.2009.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of pyruvate dehydrogenase kinase isoform 4 (PDK4) gene expression by glucocorticoids and insulin

Abstract: The pyruvate dehydrogenase complex (PDC) catalyzes the conversion of pyruvate to acetyl-CoA in mitochondria and is a key regulatory enzyme in the oxidation of glucose to acetyl-CoA. Phosphorylation of PDC by the pyruvate dehydrogenase kinases (PDK) inhibits its activity. The expression of the pyruvate dehydrogenase kinase 4 (PDK4) gene is increased in fasting and other conditions associated with the switch from the utilization of glucose to fatty acids as an energy source. Transcription of the PDK4 gene is ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 58 publications
(87 reference statements)
5
91
0
1
Order By: Relevance
“…Chromatin Immunoprecipitation Assays-ChIP assays were conducted with modifications following the protocol given by the Millipore Magna ChIP kit (17-610) (42). Rat primary hepatocytes were maintained for 18 h in RPMI 1640 medium containing 5% fetal bovine serum and 5% calf serum.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chromatin Immunoprecipitation Assays-ChIP assays were conducted with modifications following the protocol given by the Millipore Magna ChIP kit (17-610) (42). Rat primary hepatocytes were maintained for 18 h in RPMI 1640 medium containing 5% fetal bovine serum and 5% calf serum.…”
Section: Methodsmentioning
confidence: 99%
“…After treatment, cross-linking was performed with 1% formaldehyde for 10 min at room temperature, and cells were sonicated as described previously (42). Chromatin preparations were diluted with dilution buffer and protease inhibitor mixture and designated as input samples (no antibody) or immunoprecipitated with the control antibody rabbit IgG (sc-2027, Santa Cruz Biotechnology), anti-C/EBP␤ (sc-150, Santa Cruz Biotechnology), or anti-TR␤ (MA1-216, Thermo Scientific).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The isoform PDK4 is highly expressed in liver, heart and skeletal muscle and is regulated by exercise. Its expression is elevated with diabetes, fasting and other conditions associated with the switch from the utilization of glucose to fatty acids as an energy source [32,33]. It has been suggested that insulin resistance is associated with dysregulation of the PDC in skeletal muscle and that excess insulin would on the other hand down-regulate the expression of PDK4 [25,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a group of genes involved in OXPHOS and known to be downregulated in human diabetic muscle, are direct targets of PGC1a, an action that is dependent on the presence of ERRa. (53) ERRa may also control mitochondrial glucose oxidation to acetyl-coenzyme A (CoA) via the regulation of the pyruvate dehydrogenase kinases 2 and 4 (PDK2-4) in adipocyte and hepatoma cells, respectively, inducing a decrease in the conversion of pyruvate to acetyl-CoA in mitochondria and implicating ERRa as a negative regulator of the oxidation of glucose to acetyl-CoA (54)(55)(56)(57)(58) (Fig. 3).…”
Section: Erra Target Genes and Interacting Proteins That May Impact Bonementioning
confidence: 99%